Comparison of risky decision-making and evaluation of riskiness of women and men - Endriulaitienė, Auksė (Psichologija, 1998)
It was noticed that there are not consistent findings about specificity in risky decision-making among women and men. For this reason, the research of gender differences in risky decision-making and the perception of risk was conducted. Two different techniques (paired-comparisons method and choosing risky or safe decision of problem situation) were used in order to find if men are more risk-taking than women and if they rate risky work situations in the same manner as women. The subjects were ninety working students from Lithuanian universities. The results were inconsistent. In some cases men were more risk-taking than women, but the ratings of risky work situations were very similar for both - men and women. The advantages and limitations of the research, possible reasons for inconsistent results were discussed and the suggestions for future research were given.
Keywords: risky decision making; gender differences